Annual Plan 1999-2000 (Scheme-Wise Details) Union Territory of Pondicherry - Planning Commission (Planning Commission, 1999)
The territory of Pondicherry merged Indian Union with effect from 1-11-1354 in accordance with the effect to agreement between the Government of India and have Government of France, which was signed on 21-10-1954. De are transfer of Pondicherry took place on 16th August, 1962. Thereafter the Union Territory of Pondicherry consisting of the regions of Pondicherry, Karaikal, Mahe and Yanam has been administered under the provisions of Government of Union Territories Act, 1963.
Government of Pondicherry Planning and Research Department